Formulation of controlled release gellan gum macro beads of amoxicillin - Babu R.J.; Sathigari S.; Kumar M.T.; Pandit J.K. (My University, 2025)
Gellan gum has been reported to have wide pharmaceutical applications such as tablet binder, disintegrant, gelling agent and as a controlled release polymer. Multiparticulate delivery systems spread out more uniformly in the gastrointestinal tract and reduce the local irritation. The purpose of this study is to explore possible applicability of gellan macro beads as an oral controlled release system of a sparingly soluble drug, amoxicillin. Gellan gum beads were prepared by ionotropic gelation with calcium ions. The effect of drug loading, stirring time, polymer concentration, electrolyte (CaCl2) concentration, curing time etc. influencing the preparation of the gellan gum macro beads and the drug release from gellan gum beads were investigated in this study. Optimal preparation conditions allowed very high incorporation efficiency for amoxicillin (91%) The release kinetics of amoxicillin from gellan beads followed the diffusion model for an inert porous matrix in the order: 0.1 N HCl > phosphate buffer > distilled water. Change in curing time did not significantly affect the release rate constant, but drug concentration, polymer concentration and electrolyte concentration significantly affect the release rate of amoxicillin from the beads. The gellan macro beads may be suitable for gastro retentive controlled delivery of amoxicillin. © 2010 Bentham Science Publishers Ltd.